2014
DOI: 10.1177/230949901402200213
|View full text |Cite
|
Sign up to set email alerts
|

Fixation with Cancellous Screws and Fibular Strut Grafts for Neglected Femoral Neck Fractures

Abstract: Purpose. To review the outcomes of fixation with cancellous screws and fibular strut grafts for neglected femoral neck fractures. Methods. 44 men and 28 women aged 17 to 50 years with neglected femoral neck fractures of the subcapital (n=12), transcervical (n=57), or basal (n=3) types underwent closed (n=39) or open (n=33) reduction and fixation with a single cancellous screw with double fibular strut grafts (n=24) or fixation with double cancellous screws with a single fibular strut graft (n=48). The mean tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The definition of neglected femoral neck fracture varies in these articles. Nine articles reported more than 3 weeks of delay as neglected, 17 23 24 26 27 28 29 30 32 whereas remaining articles mentioned more than 6 weeks as the definition of neglected fracture. 19 25 31 However, the definition of nonunion is quite clear.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of neglected femoral neck fracture varies in these articles. Nine articles reported more than 3 weeks of delay as neglected, 17 23 24 26 27 28 29 30 32 whereas remaining articles mentioned more than 6 weeks as the definition of neglected fracture. 19 25 31 However, the definition of nonunion is quite clear.…”
Section: R Esultsmentioning
confidence: 99%
“… 22 23 28 29 30 31 32 Five articles reported CR where possible and OR when CR failed. 20 21 24 25 26 The authors supporting OR assert that by opening the nonunion site, the interposed fibrous tissue between the fracture fragments can be removed. Moreover, the fracture ends can be freshened, and the neck-shaft angle can be adjusted.…”
Section: R Esultsmentioning
confidence: 99%
“…However, their use was associated with some complications such as donor site pain, graft fracture, and gait pattern modification (15,23,(29)(30)(31). We preferred to avoid the use of fibular strut graft considering the risk of gait impairment as reported in literature (31).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…We preferred to avoid the use of fibular strut graft considering the risk of gait impairment as reported in literature (31). Several Authors showed good outcomes using cannulated screws associated with both fibular strut graft (29,30,32) and cancellous bone graft (33). Recently, a biomechanical study demonstrated that placing a third cannulated cancellous screw in the calcar provide a stability advantage for femoral neck fractures fixation (34).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…C) vascularized fibular graft have been advocated along with or without internal fixation along with valgus osteotomy to treat neglected fractures and ununited femoral neck fractures to promote union. [5][6][7][8][9][10][11][12][13][14][15][16][17] Bone graft supplementation by using free fibular grafting was in past used in fifth decade but with less satisfying results. [18][19][20] In India it was revived in 1981 and first results were published in 1986.…”
Section: Introductionmentioning
confidence: 99%